Why women build less effective networks than men: The role of structural exclusion and personal hesitation. (July 2019) - Greguletz, Elena; Diehl, Marjo-Riitta; Kreutzer, Karin
Studies have shown that women's professional networks are often less powerful and effective than men's in terms of exchanged benefits, yet the motivations that underlie the networking behaviours remain less well understood. Based on an interview study of 37 high-profile female leaders working in large German corporations, we found that not only the extrinsic barrier of structural exclusion from powerful networks, but also the intrinsic barrier of women's hesitations to instrumentalize social ties are key to answering our research question: Why do women build less effective networks than men ? Our analysis points to the existence of structural exclusion resulting from work–family conflict and homophily. With regard to personal hesitation, we identified two elements that were associated with under-benefiting from networking: moral considerations in social interactions and gendered modesty. Our study makes two important contributions. First, by highlighting personal hesitation as an intrinsic barrier, it extends the understanding of women's motivations for networking based on social exchange theory. Second, based on structural barriers and personal hesitation, it develops a grounded theory model of networking that offers a holistic understanding of reasons that, from the perspective of the focal women, contribute to gender inequality in the workplace.